2016
DOI: 10.1007/s00709-016-1063-y
|View full text |Cite
|
Sign up to set email alerts
|

Genomic effects of glucocorticoids

Abstract: Glucocorticoids and their receptor (GR) have been an important area of research because of their pleiotropic physiological functions and extensive use in the clinic. In addition, the association between GR and glucocorticoids, which is highly specific, leads to rapid nuclear translocation where GR associates with chromatin to regulate gene transcription. This simplified model system has been instrumental for studying the complexity of transcription regulation processes occurring at chromatin. In this review we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 95 publications
1
22
0
Order By: Relevance
“…4f). Previous studies have shown that GR sites are overall accessible prior to GR activation and that this accessibility increases in a subset of loci following GR binding (2,5,10,32,(51)(52)(53). Our results here show that hormone treatment elevates chromatin accessibility specifically at GR sites associated with GR-activated genes.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…4f). Previous studies have shown that GR sites are overall accessible prior to GR activation and that this accessibility increases in a subset of loci following GR binding (2,5,10,32,(51)(52)(53). Our results here show that hormone treatment elevates chromatin accessibility specifically at GR sites associated with GR-activated genes.…”
supporting
confidence: 68%
“…While significant progress has been made in understanding how these regulatory sites are initiated and maintained, less is known about the mechanisms that determine the specific function of GR sites in activating or repressing transcription. Gene activation is thought to be primarily controlled by direct binding of GR to its recognition element (GRE) and subsequent recruitment of co-activators such as SRC-1, GRIP1 and CBP/EP300 (7)(8)(9)(10). Models for transcriptional repression include direct and indirect GR binding to DNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the cells were treated with the synthetic ligand dexamethasone (Dex) prior to imaging. Dex binds to the ligand-binding pocket of the GR which induces the nuclear translocation of the receptor, and results in chromatin binding and subsequent regulation of transcription [30]. Using a custom made tracking software (see section 2.3), individual localizations of single molecules are classified as belonging to a bound track segment (i.e.…”
Section: Single-molecule Tracking For Extracting Binding Charactermentioning
confidence: 99%
“…These results reflect the complex relationship between gene regulation and genome architecture, as evident for other regulatory layers of gene transcription. For example, TF binding may promote, inhibit, or potentiate gene transcription [41,42]. Thus, to define the molecular basis of genome architecture during adipogenesis, we searched for coordinated dynamics between genome reorganization and other chromatin processes (e.g., histone modifications and TF binding).…”
Section: Spatial Compartmentalization Of the Adipogenic Genetic Programmentioning
confidence: 99%